2017
DOI: 10.1186/s13256-017-1457-2
|View full text |Cite
|
Sign up to set email alerts
|

Urethrovaginal fistula following vaginal prolapse of a pedunculated uterine myoma: a case report

Abstract: BackgroundUrethrovaginal fistulas are usually secondary to a foreign body in the vagina or to vaginal gynecologic surgeries. We present a case of an urethrovaginal fistula secondary to vaginal prolapse of a huge pedunculated submucosal uterine myoma.Case presentationA 25-year-old black African woman with a past history of huge uterine fibroids and an uncomplicated vaginal delivery 5 weeks prior to presentation consulted for a difficult micturition that occurred 2 days earlier. A vaginally prolapsed huge uterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Other rare complications are vaginal prolapse with compression of the bladder neck or the urethra with resulting urinary retention, as in our case. Urethrovaginal fistula is possible; our patient developed it later [ 7 ]. Vaginal prolapse of a fibroid can also occur following uterine artery embolization for uterine fibroids [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other rare complications are vaginal prolapse with compression of the bladder neck or the urethra with resulting urinary retention, as in our case. Urethrovaginal fistula is possible; our patient developed it later [ 7 ]. Vaginal prolapse of a fibroid can also occur following uterine artery embolization for uterine fibroids [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal prolapse has been documented in cattle, goats, sheep, camels, dogs, cats, and women. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] To authors' knowledge, it has not been reported in mares. A mare had cervical hyperplasia and mass that led to vaginal protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Other factors include, excess perivaginal fat, prior perivaginal tissue injury, poor conformation, and incompetence of the constrictor vestibule or vulvae musculature. 4,6,8,9 Vaginal prolapse most commonly occurs in multiparous women among the ages of 40 -70. [7][8][9] In most species, it occurs during the last few weeks of pregnancy when intraabdominal pressure is maximum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation